Spermatogenesis and karyotypes of three species of water striders (Gerridae, Heteroptera). - Castanhole, M. M.; Pereira, L. L.; Souza, H. V.; Itoyama, M. M. (Genetics and Molecular Research, 2010)
Although they are of economic importance, there have been few cytogenetic studies of the Gerridae (Heteroptera) in Brazil. We examined spermatogenesis (meiosis and spermiogenesis) and nucleolar behavior in three species of the family Gerridae. Brachymetra albinerva and Halobatopsis platensis were found to have a chromosome complement of 2n = 25 (24A + X0) and Cylindrostethus palmaris 2n = 29 (28A + X0) chromosomes. Fifteen individuals of these species were collected from the reservoir of São José do Rio Preto, SP, using screens and were transported in pots containing water to the laboratory, where cytogenetic preparations were made. The polyploidy nuclei are formed by several heteropyknotic regions; cells in meiotic prophase have a heteropyknotic region that is probably the sex chromosome, and the chromosomes from chiasmata. The spermatids are rounded and have a heteropyknotic region at the periphery of the nucleus; the sperm head is small, with a long tail. Silver impregnation of meiotic cells showed one or more disorganized bodies around the perichromosomal sheath. The round spermatids had two bodies next to each other, but these were elongated; one of the bodies remained in the head and the other migrated to the initial part of the tail at the end of spermagenesis, when the staining was no longer evident. The meiotic cells appear during spermatogenesis and have very similar silver-impregnation patterns in different species of Heteroptera.
Keywords: silver; animal; classification; cytology; genetics; Heteroptera; karyotyping; male; meiosis; seminiferous tubule; spermatogenesis; Animals; Karyotyping; Male; Meiosis; Seminiferous Tubules; Silver; Spermatogenesis